Routing Taxonomies for Network Aware Territory of Vehicles: A Review (International Journal of Engineering and Computer Science, 2017)
In this task we aim to provide a through global taxonomy of VANET routing protocols. This task also aims to provide a simulation test bed enabling performance assessment of the protocols. This work also complements the previous approaches of classification. Characteristically we acknowledged following taxonomical routing protocols classification, based on their transmission approach, based on their prerequisite knowledge needed to realize routing, based on their delay sensitivity and toleration, based on their accommodating network i.e., heterogeneous and homogeneous vehicular network environment and based on their inspiration i.e., bio-inspired algorithms. Evaluation of a routing protocol in VANET is a necessary, indispensable and struggling task, so we bring assessment methods, i.e., simulation and real world research into the picture. Once the protocol passes all the simulation tests with expected results then it can be tested in the real time vehicular environments. All of this work provides a base for VANET research community to excogitate a new routing techniques